2018
DOI: 10.1063/1.5023623
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the multiple harmonics by step-like cantilever

Abstract: In atomic force microscopy (AFM), the higher modes are highly sensitive to the tip-sample interactions which generate many harmonics. When a higher harmonic is close to the natural frequency of a mode, the harmonic signal is enhanced by a resonance. The step-like cantilever is proposed as an effective design to enhance the higher harmonic signals. The natural frequencies are changed with the variations of the step-like cantilever sizes. By carefully designing the step-like cantilever, the first three modes can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Actually there are three more veering loci as indicated by the arrows, which are formed by the veering. Physically, the variation of the overhang length ( ) changes the mass and stiffness distribution of the system and its impact on different mode is different [ 19 ], which is clearly seen in the wavy variations in Figure 2 . As the two overhangs here are identical, there is only one control parameter, i.e., .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Actually there are three more veering loci as indicated by the arrows, which are formed by the veering. Physically, the variation of the overhang length ( ) changes the mass and stiffness distribution of the system and its impact on different mode is different [ 19 ], which is clearly seen in the wavy variations in Figure 2 . As the two overhangs here are identical, there is only one control parameter, i.e., .…”
Section: Resultsmentioning
confidence: 99%
“…The other twelve are at the two connecting points at and . Physically, these twelve equations are to ensure the continuity of displacement, slope, moment and shear force at the two connecting points [ 19 ]. The governing equation of the overhang–beams–overhang structure is divided into four in three domains, as indicated by Equation ( 3 ).…”
Section: Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection using high-harmonic frequencies Atomic force microscope (AFM) with the microcantilever as central nowadays is becoming a conventional device in the detection of micro to nano-objects that helps to reveal the physical and chemical properties in nanoscale. [1][2][3][4][5] Several studies have been adopted to enhance the functionality of the cantilever via changing its cross-section materials [6][7][8][9][10] and dimensions [11][12][13][14][15] and revealed that the sensitivity of the cantilever sensor could be enhanced if higher modes of oscillation are used [16][17][18][19] and the quality factor could be increased, especially when functioned in liquids. 20,21) This is explained by the fact that the surface-to-bulk ratio is lower at higher-order modes, which leads to lower air/fluid damping.…”
mentioning
confidence: 99%
“…Therefore, several efforts have been used to efficiently excite the functionality of the higher modes such as adding another test mass, 22) etching an extra magnetic layer 21) to a specific position on the cantilever, selectively exciting the photo-thermal effect by tuning the heat position, 23,24) facilitating a tip-sample interaction that could alter the stiffness of the cantilever, or changing the cross-section. 7,11) Among that, changing the surface geometry to change the cross-section has been examined in several experiments where one [13][14][15] or two 12) holes were made on the cantilever surface by milling a small cantilever on the interior of a standard cantilever. 25) These holes alter the flexural effective mass of the cantilever and lead to a change in the cantilever frequencies.…”
mentioning
confidence: 99%